Citation analysis of Acta Pharmacologica Sinica 1984-1989 - LI Cheng-jian; KE Yin-hua; YU Ke-ning; DU Gui-hua; WANG Ju-rong; ZHANG Hui; ZHANG Hong-sheng (Acta Pharmacologica Sinica; Vol 11, No 1 (January 1990): Acta Pharmacologica Sinica, 2016)
Citation analysis was made bibliometrically on the collection and dispersion of the references in Acta Pharmacologica Sinica 1984-1989. Core periodicals were sorted out: 31 in foreign languages and 6 in Chinese. Suggestions are proposed to the information services.